Observational study of differences in head position for high notes in famous classical and non-classical male singers. (2nd April 2016) - Amarante Andrade, Pedro; Švec, Jan G.
Abstract : Introduction. Differences in classical and non-classical singing are due primarily to aesthetic style requirements. The head position can affect the sound quality. This study aimed at comparing the head position for famous classical and non-classical male singers performing high notes. Method. Images of 39 Western classical and 34 non-classical male singers during live performances were obtained from YouTube. Ten raters evaluated the frontal rotational head position (depression versus elevation) and transverse head position (retraction versus protraction) visually using a visual analogue scale. Results. The results showed a significant difference for frontal rotational head position. Discussion and conclusion. Most non-classical singers in the sample elevated their heads for high notes while the classical singers were observed to keep it around the neutral position. This difference may be attributed to different singing techniques and phonatory system adjustments utilized by each group.